2018
DOI: 10.14295/bds.2018.v21i4.1600
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic therapy as a novel approach in the prevention and treatment of gingivitis. A review

Abstract: <p>Gingivitis is caused by a mixture of Gram-positive and Gram-negative species and is characterized by inflammatory exudate in the marginal region. Probiotics have been introduced in the prevention and treatment of periodontal diseases and represent an innovative approach to maintaining oral health using beneficial bacteria when administered in adequate amounts. The mechanism of action of probiotics in the oral cavity is not fully understood but is commonly explained by a combination of local and system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In this scenario, probiotics use were considered for the treatment of gingival and periodontal conditions [15,16]. The mechanisms related to the use of probiotics are the host's immunoinflammatory modulation [17], the attenuation of periodontal pathogen-induced interleukins expression in epithelial oral cells [18], and the reduction of pro-inflammatory cytokines [19].…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, probiotics use were considered for the treatment of gingival and periodontal conditions [15,16]. The mechanisms related to the use of probiotics are the host's immunoinflammatory modulation [17], the attenuation of periodontal pathogen-induced interleukins expression in epithelial oral cells [18], and the reduction of pro-inflammatory cytokines [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that probiotic microorganisms have a vital participation in the prevention of different oral diseases when consumed regularly [ 15 ]. Intensive research on the properties of probiotics in maintaining ecological equilibrium and efficiently normalizing the oral microbiota has been an essential subject for many years [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%